2019
DOI: 10.1016/j.ecolmodel.2018.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem services accounts: Valuing the actual flow of nature-based recreation from ecosystems to people

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(74 citation statements)
references
References 27 publications
0
70
0
4
Order By: Relevance
“…Cultural ecosystem services from recreation and nature-based tourism feature strongly in much of the debate about ecosystem contributions to human wellbeing, sustainable development, and green economy transitions. On the one hand, several studies have suggested that such ecosystem services can contribute to a range of constituents of human wellbeing, such as physical and mental health [11,12], while supporting local and national economic growth [13,14]. On the other hand, there has been criticism about the negative effects of nature-based tourism on fragile ecosystems and protected areas [15] and the elite's monopolization of the benefits accrued from tourism [16].…”
Section: Introductionmentioning
confidence: 99%
“…Cultural ecosystem services from recreation and nature-based tourism feature strongly in much of the debate about ecosystem contributions to human wellbeing, sustainable development, and green economy transitions. On the one hand, several studies have suggested that such ecosystem services can contribute to a range of constituents of human wellbeing, such as physical and mental health [11,12], while supporting local and national economic growth [13,14]. On the other hand, there has been criticism about the negative effects of nature-based tourism on fragile ecosystems and protected areas [15] and the elite's monopolization of the benefits accrued from tourism [16].…”
Section: Introductionmentioning
confidence: 99%
“…We have defined the environmental income in previous publications as the total contribution of nature to the total income of an economic activity in the period [2][3][4]32]. In regard to the measurement of these two ecosystem variables, here, we limited this aspect to the presentation of comparisons of the ecosystem service valuations and the changes in environmental assets by a small sample of authors, thus illustrating the similarities and differences in the valuations of woody products (timber, cork, and firewood) [3,4,8,33], carbon [3,27,33], free access recreational services [3,5,22,34], and the environmental income [27,29,30,[35][36][37].…”
Section: Brief Review Of the Literature On Ecosystem Services And Envmentioning
confidence: 99%
“…Other authors have preferred to estimate the ES of woody products from the net natural physical growth in the period of the woody products in progress. These authors have explained that this is "in order to avoid misleading overlapping and double counting between the ecosystem service and economic activities already captured by the economic accounts" [34] (p. 9).…”
Section: Woody Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Luisetti et al [4] used a scenario analysis to study carbon storage and carbon emissions in marine habitats in the UK; Petitgas et al [10] developed a marine ecological data system based on multi-table analysis to describe and detect spatial structures in ecosystems; Halouani et al [11] employed OSMOSE models and Eco3M-Med Models to develop new indicators to assess the impact of fishing activity on marine ecosystems; Hong et al [12] used wavelet power and coherence spectrum, coupled ecosystem functions and monsoon climates to explore both the carbon and water exchange in ecosystems under monsoon disturbances; Mao et al [13] quantified the natural wetland-farm conversion to study the natural wetland and farmland space-time patterns under the influence of agricultural activities; Culhane et al [14] evaluated the 'risk to ecosystem service supply' (RESS) of 99 aquatic ecosystems. Vörösmarty et al [15] proposed ecosystem-based water security and sustainable development; Vallecillo et al [16] applied environmental economic accounting system-test ecosystem accounting (SEEA-EEA) for 2012 nature recreational activities and developed ecosystem service accounts to measure changes in natural capital; Villarreal et al [17] used the Ecosystem Functional Type (EFTS) method to evaluate whether vortex covariance sites are providing adequate representation, and used their combined core sites to address questions regarding decadal and inter-annual variability of ecosystem functional heterogeneity across the contiguous United States; Bernués et al [18] studied the relationship between farmers and non-farmers on agriculture and the environment in high-value farmland, and explored the sustainability of farmland ecosystem services; Weitzman et al [19] analyzed the status of aquaculture research in recent years, and in doing so, called attention to the application of the ecosystem services frameworks to promote sustainable development and recognized that aquaculture is closely related to ecosystems; Ron I et al [20] used the Bayesian network to simulate ecosystem services and explored the applicability and flexibility of the model in ecosystem services; Hooper et al [21] investigated how the sensitivity assessment can be applied to ecosystem services by considering the relationship between the sensitivity of the service and the sensitivity of the habitat in which it is supplied; Firbank et al [22] explored how closed farm ecosystem services can meet the needs of humanity in the future; Leung et al [23] proposed an ecosystem framework for the sustainable development of shared economic ecosystems; Danilo et al [24] provided new insights into the experimental method for assessing the actual size of the ecosystem service by studying the resistance of bats to agro-ecosystems.…”
Section: Introductionmentioning
confidence: 99%